Critical Insights from Social Workers on Adolescents’ Engagement in Alternative Religious Movements: Media as a Problematic Socialising Environment - Tkáčová, Hedviga; Leskova, Andrea; Rashidovich Khazratkulov, Mutallib (Journal of Education Culture and Society, 2025)
Aim. This study examines the effects of Alternative Religious Movements (ARM) on adolescents, aiming to address a research gap by providing qualitative insights into social workers’ perspectives on (1) the outcomes of adolescents’ positive perceptions of ARM and (2) the potential influence of social media on their views of ARM. Methods. Focus Group with six experienced social workers provided insights into adolescents’ resilience against ARM. Thematic analysis revealed key consequences and examined the role of social media in shaping adolescents’ perceptions of ARM. Results. Consequences of ARM involvement included behavioural changes, social isolation, weakened relationships, reduced critical thinking, and dependency on the controversial group. Additionally, the study highlighted the significant role of social media in amplifying the accessibility of ARM content and facilitating adolescents’ engagement with these groups through virtual communities. Conclusion. The study highlights the necessity for targeted preventive strategies in social work to address the consequences of adolescents’ positive perceptions of ARM, such as behavioural changes, social isolation, and reduced critical thinking. It also underscores the pivotal role of social media in shaping adolescents’ religious identities and emphasises the need to guide them through these influences. Cognitive Value. This research enhances the understanding of ARM’s impact on adolescents and stresses the importance of targeted interventions. It provides practical insights into protecting vulnerable youth, navigating online environments, and comprehending the “mediatisation of religion” in shaping spiritual identities.